Developmental Peculiarities and Seed-Borne Endophytes in Quinoa: Omnipresent, Robust Bacilli Contribute to Plant Fitness - Pitzschke, Andrea (Frontiers in Microbiology, 2016)
Among potential climate change-adapted crops for future agriculture, quinoa (Chenopodium quinoa), a facultative halophyte plant with exceptional nutritional properties, stands out as a prime candidate. This work examined how quinoa deals with extreme situations during seed rehydration. A seed-borne microbiome was discovered and its potential role in early development and stress resistance investigated. Methods involved germination and drought exposure assays, histochemical detection of reactive oxygen species, and diverse tests with seed(ling) material to assess microbial occurrence, release and proliferation. Quinoa´s microbial partners were biochemically, microscopically and taxonomically characterized. Quinoa distinguishes itself from other plants in multiple ways. It germinates within minutes, even under extremely hostile conditions. Broken seeds/split embryos are able to regenerate. Furthermore, quinoa seedlings are resurrection-competent. These peculiarities became in part explainable upon discovery of seed-borne microorganisms. 100% of quinoa seeds, from different sources, are inhabited by bacteria of the genus Bacillus. These endophytes are mobile and reside in all seedling organs, indicating vertical transmission. Owing to their strong catalase activity and high superoxide contents they can modify host redox properties. One outcome is cell expansion, enabling quinoa to overcome a critical period in development, seedling establishment. Quinoa´s immediate confrontation with “foreign” ROS and bacterial elicitors likely induces a naturally primed state, enabling plants to withstand extreme situations. The endophytic bacteria, which are cultivable and highly robust themselves, have high potential for application in agriculture, food (amylase) and cosmetics (catalase) industry. An exciting question arising from this work is: Can quinoa´s microbiome be transferred to improve stress resistance in other plant species?